Nova estratégia para análise de contaminantes emergentes em águas residuais industriais por espectrometria de massas ambiente (PSI-MS) - Rodrigues, Marcella Ferreira (2018)
Water is an essential natural resource for life that is compromised by the release of emerging contaminants, including synthetic hormones. These compounds can be released directly through industrial effluents and indirectly through domestic sewage. Monitoring emergent contaminants (ECs) in the aquatic environment has become a priority as they pose risks to human health and the environment because of their ability to deregulate the endocrine system. Thus, verification analyzes of the emerging contaminants produced by the pharmaceutical industries are required. The most common analytical methods for analysis of this class of compounds involve the use of liquid or gas chromatography coupled to tandem mass spectrometry (MS / MS) with procedures for the preparation of long samples and long chromatographic runs. In this study, a methodology was developed for the analysis of emerging contaminants in raw and treated industrial wastewater from a local industry's hormone production line by an environmental ionization technique known as Paper Spray Ionization (PSI). Here, we have proposed an analytical approach based on the use of waxed papers. Analyzes of the synthetic hormones levonorgestrel and algestone acetophenide occurred by adding the sample to a triangular paper that was moistened with methanol solution (0.1% formic acid). The paper was fixed at the input of the mass spectrometer through a metal clip which provided a voltage to the paper. The analytical curves presented a linear correlation coefficient above 0.99. For the hormone levonorgestrel the intra-day and inter-day precision ranged from 0.5 to 5.3%, accuracy ranged from -7.0 to 4.2% while recovery ranged from 82.2 to 101.3%. For the hormone algestone acetophenide the intra-day and inter-day precision ranged from 0.9 to 10.7%, accuracy ranged from -7.7 to 8.9% while recovery ranged from 88.4 to 101.6%. The levonorgestrel hormone was also analyzed with the classic LC-MS method, showing consistent results between the two approaches, thus confirming the reliability of the proposed method.